Promotion Prospects and Within-level Wage Growth: A Decomposition of the Part-time Penalty for Women - Boryana Ilieva (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
I study the life-cycle pattern of part-time employment and its impact on wage growth in female careers. I show that the part-time wage penalty consists of two essential components: i) a penalty for promotions and ii) a within-career-level wage penalty. Using dynamic structural modeling, I quantify the relative importance of the channels. The penalty for working half a day for two consecutive years in one's early thirties is one Euro per hour. 70% of it is due to slowdowns in experience accumulation within career levels. A part-time spell of four years marks the point at which forgone chances of promotion and within-level wage losses contribute to the wage penalty to an equal degree. Counterfactual simulations demonstrate that financial incentives to increase the time spent working can be well complemented by policies which ensure that experienced young women are promoted early in their careers.
Keywords: J21; J21; J24; J31; 330; wage growth; female labor supply; part-time employment; promotions